Dynamics of Learning Motivation Among Slow-Learning Students in The Teaching of Multiplication Tables in The Fourth Grade of Elementary School - Aisyah Falah Agdiyah; Ima Mulyawati (FKIP - Universitas Riau, 2026)
Learning motivation is important in mathematics learning; however, little is known about how slow learners' motivation changes during instruction. This study aims to describe and understand the dynamics of slow learners' motivation during repeated multiplication learning in a fourth-grade class at a public elementary school in East Jakarta. Data were collected through observation, semi-structured interviews, and documentation and analyzed using Miles and Huberman's interactive model. The findings indicate that slow learners' motivation is dynamic, influenced by task difficulty, learning strategies, instructional media, teacher guidance, and parental support. Motivation increases through the use of concrete materials, repeated explanations, step-by-step guidance, and positive reinforcement but decreases when students encounter more complex tasks. The study also found that adaptive mathematics instruction and continuous parent teacher collaboration are essential for sustaining slow learners' motivation. These findings contribute to the literature by explaining the dynamics of slow learners' motivation during repeated multiplication learning, complementing previous studies that primarily focused on instructional strategies or learning outcomes.